PENGARUH PENGELOLAAN ZAKAT DAN WAKAF TERHADAP PENGURANGAN KEMISKINAN DI KABUPATEN CIANJUR - Halimatussadiah, Shida; Sulastri, Lilis (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
This research is based on the framework of thinking that there is a positive and significant influence between zakat and waqf management on poverty reduction in Cianjur district. This research uses descriptive analysis method. The sample in this study is data from the Baznas report in Cianjur district and BWI in Cianjur district for a period of 7 years from 2013 to 2019. Data analysis in this study uses validity test, reliability test, classical assumption test, multiple linear analysis test, coefficient of determination test, test of t (partial), and F test (simultaneous). The results of this study indicate that there is an insignificant positive effect of zakat management on poverty reduction, as indicated by the t value for the zakat management variable (1.307) which is smaller than t table (2.776) at a significance level of 0.05. Then, there is a positive and significant effect of waqf on poverty reduction, as indicated by the t-count value of the waqf variable (4.145) which is greater than the t-table value (2.776) at a significance level of 0.05. There is an effect of simultaneous management of zakat and waqf on poverty reduction in Cianjur district. This is indicated by the comparison of the calculated F value (8.727) which is greater than the F table value (6.994) at a significance level of 0.05. Keywords: Poverty, zakat management, waqf, economic development